Organizational Justice as a Predictor of Organizational Citizenship Behavior and Employee Engagement in the Healthcare Sector: A conceptual study - Gayathri G; A Savarimuthu (Asia Pacific Journal of Health Management)
The healthcare sector framework highlights the importance of organizational justice in shaping employee attitudes and behaviors within healthcare settings. It emphasizes that perceptions of fairness—encompassing distributive, procedural, and interactional justice—are crucial for fostering (OCB) and enhancing employee engagement, ultimately impacting the quality of patient care and organizational effectiveness. This research aims to examine the impact of organizational justice on organizational citizenship behavior (OCB) and employee engagement among healthcare professionals. The study emphasizes the critical role that perceptions of fairness play in enhancing employee morale and productivity within healthcare settings.